Case report: Aggressive progression of acute heart failure due to juvenile tuberculosis-associated Takayasu arteritis with aortic stenosis and thrombosis - Xuan, Wenjie; Wang, Zhaoling; Lin, Jinjing; Zou, Lixia; Xu, Xisheng; Yang, Xinghui; Xu, Yiping; Zhang, Yan; Zheng, Qi; Xu, Xuefeng; Lu, Meiping (Frontiers in Cardiovascular Medicine, 2023)
Background Takayasu arteritis (TA) is a chronic granulomatous vasculitis with unknown pathophysiology. TA with severe aortic obstruction has a poor prognosis. However, the efficacy of biologics and appropriate timing of surgical intervention remain controversial. We report a case of tuberculosis (TB)-associated TA with aggressive acute heart failure (AHF), pulmonary hypertension (PH), thrombosis, and seizure, who failed to survive after surgery. Case presentation A 10-year-old boy who developed a cough with chest tightness, shortness of breath, hemoptysis with reduced left ventricular ejection fraction, PH, and increased C-reactive protein and erythrocyte sedimentation rate was hospitalized at the pediatric intensive care unit of our hospital. He had strongly positive purified protein derivative skin test and interferon-gamma release assay result. Computed tomography angiography (CTA) showed occlusion of proximal left subclavian artery and stenosis of descending aorta and upper abdominal aorta. His condition did not improve after administration of milrinone, diuretics, antihypertensive agents, and intravenous methylprednisolone pulse followed by oral prednisone. Intravenous tocilizumab was administered for five doses, followed by two doses of infliximab, but his HF worsened, and CTA on day 77 showed complete occlusion of the descending aorta with large thrombus. He had a seizure on day 99 with deterioration of renal function. Balloon angioplasty and catheter-directed thrombolysis were performed on day 127. Unfortunately, the child's heart function continued to deteriorate and died on day 133. Conclusion TB infection may be related to juvenile TA. The biologics, thrombolysis, and surgical intervention failed to achieve the anticipated effect in our case with aggressive AHF due to severe aortic stenosis and thrombosis. More studies are needed to determine the role of biologics and surgery in such dire cases.